Global institutions: Governance reform for food, nutrition, and agriculture - von Braun, Joachim (International Food Policy Research Institute, 2018)
As food and agricultural systems become increasingly globalized, the policy and governance issues related to food and nutrition security are becoming more complex. New and growing complexities require more systematic, coordinated, and evidence-based responses. Among these complexities is the need for diplomacy and security interventions to prevent hunger in conflict- and war-affected zones. Another complexity is the triple burden of malnutrition— undernutrition, micronutrient deficiencies and other diet quality problems, and obesity in an increasingly urban world—all three requiring simultaneous attention but different policy responses. A third is posed by the need to address production constraints and environmental risks, including low agricultural productivity growth, climate change, increased soil and land degradation, and loss of biodiversity. Finally, food and nutrition policy must account for the complexity related to global integration through trade and investment, most notably contested positions on fair and free trade, risks of market and price volatility, food industries’ international roles, and the protection of food safety. These interwoven challenges call for global governance to improve food and nutrition security. This chapter argues that a redesign of the current global food and agricultural governance system is needed to facilitate actions for accelerated reduction of undernutrition and malnutrition.